Internalization of Behavior Management Skills among Teachers in a Specialized School Serving Students with Neurodevelopmental Disorders. Issue 4 (July 2022) - Ramsey, Kathleen L.; Smith, Stephanie D.; Hansen, Laura K.; Mohn, Richard S.; Walbridge, Fayth C.; Barajas, Kimberly G.; Ellis, Brandi M.; Dufrene, Brad A.
Prior studies suggest that the fidelity of teachers' implementation of behavior management practices in the classroom diminish over time. Establishing how long it takes teachers to fully learn and sustain their independent use of these skills may aid in addressing implementation drift. The primary goals of this pilot study were twofold: (1) determine how long it takes teachers employed at a school serving students with Neurodevelopmental Disorders to internalize evidence-based behavior management practices (i.e., positive reinforcement, direct commands), and (2) establish whether some skills take longer than others for teachers to internalize. We also had the opportunity to evaluate whether a pre-determined threshold of skill internalization (e.g., 50% increase in skill use for three consecutive weeks) as defined in the extant literature translates into sustained skill implementation. Our results suggest that the length of standard teacher trainings may not be adequate given upwards of 2 months is required for the internalization of one skill and the time needed to reach internalization is dependent upon the skill taught and may deviate by at least 2 weeks across skills. However, given the variability observed in teachers' implementation of skills following internalization, this pre-determined threshold of skill internalization may be insufficient and requires further examination in future studies.